Positive relationship between bone mineral density and low back pain in middle-aged women - Manabe, Takashi (Springer-Verlag, 2003)
There have been a large number of epidemiological studies demonstrating various primary factors that cause musculoskeletal disorders in middle-aged and older women. However, the relationship between low back pain and bone mineral density is not well documented, and no evidence for any direct relationship between the two has been found. To investigate the relationship, we conducted a cross-sectional study, on a population of 2,244 Japanese women aged 25–85 years who were participating in a regional health screening program. Information on lifestyle, reproductive characteristics and the presence of current low back pain was collected by self-administered questionnaires, and bone mineral density at the distal radius was measured. We found increasing bone mineral density to be significantly associated with low back pain in middle-aged women using a logistic regression analysis. Exercise and smoking were also significantly associated with low back pain. This association remained even after entering other lifestyle and reproductive factors into the final model. Accordingly, high bone mineral density would seem to be as important a public health problem as low bone mineral density and osteoporosis when considering the musculoskeletal symptoms and disabilities that appear in middle-aged women.